2018
DOI: 10.1159/000495718
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-15 Activates NF-κB Pathway via Down Regulating Expression of Adenosine A2 Receptor in Ulcerative Colitis

Abstract: Background/Aims: The role of miR-15 in ulcerative colitis (UC) is unclear. In this study, we found that miR-15 downregulated the expression of adenosine A2a receptor (A2aAR) in the colonic tissues of patients with UC and in HT-29 human colonic epithelial cells. Methods: The study population comprised patients with UC (n=23), irritable bowel syndrome (IBS, n=22), and healthy subjects (n = 20). The levels of miR-15, A2aAR, and protein in colon tissue biopsies were determined by real-time quantitative reverse tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…There is some evidence to demonstrate that cold inducible RNA‐binding protein preserved H9c2 cells from cardiomyocyte via inhibiting NF‐κB pathway . Many reports illustrated that many miRNAs have effects on NF‐κB pathway . According to Xing et al, miRNA‐183 could improve myocardial damage via NF‐κB signaling .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…There is some evidence to demonstrate that cold inducible RNA‐binding protein preserved H9c2 cells from cardiomyocyte via inhibiting NF‐κB pathway . Many reports illustrated that many miRNAs have effects on NF‐κB pathway . According to Xing et al, miRNA‐183 could improve myocardial damage via NF‐κB signaling .…”
Section: Discussionmentioning
confidence: 98%
“…31 Many reports illustrated that many miRNAs have effects on NF-κB pathway. 32,33 According to Xing et al, miRNA-183 could improve myocardial damage via NF-κB signaling. 34 Thus far, previous study has confirmed that upregulation of miR-27 suppressed the pathogenesis of osteoarthritis by inactivating the NF-κB pathway.…”
Section: Downregulated Expression Of Mir-27 In Myocardial Ischemia mentioning
confidence: 99%
“…Crohn's patients with active disease displayed an increased A 2A receptor mRNA expression in colonic mucosa, while no changes were observed in patients with ulcerative colitis (18). Conversely, others reported a decreased mRNA and protein expression of A 2A receptor in sigmoid colonic mucosa from active ulcerative colitis patients (19,20). In addition, the authors observed that A 2A receptor expression was oppositely related with miR-16 expression (19).…”
Section: Role Of Adenosine System In Intestinal Inflammationmentioning
confidence: 98%
“…In particular, miR-16, targeting the 3 ′ -UTR of A 2A receptor mRNA, has been found to inhibit A 2A receptor transcription (19). Zhang et al (20) observed a correlation between the increase in miR-15 and a decreased expression of A 2A receptor mRNA in colonic tissues from ulcerative colitis patients. The authors demonstrated in HT-29 cell lines that miR-15 downregulated A 2A receptor mRNA expression, which, in turn, decreased the activation of pro-inflammatory NF-κB signaling (20).…”
Section: Role Of Adenosine System In Intestinal Inflammationmentioning
confidence: 99%
“…In general, miRNAs play an inhibitory role in tumors and various diseases . However, some studies have shown that some miRNAs can promote the progress of cancers and a variety of other diseases . miR‐922 is considered to be a tumor‐promoting gene, which can promote the occurrence and progress of tumor.…”
Section: Introductionmentioning
confidence: 99%